STUDIES ON EFFECT OF THIMET ON AGROMYZID PEST CHROMA TOMYIA HORTÍCOLA (GOUR.) ON LYCOPERSICON ESCULENTUM (LINN.) - SINGU, NEETU; PALIWAL, A.K.; SINGH, SURENDRA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2009)
The experimental work was done in Zoology Department Ganjdundwara College, Ganjdundwara, Etah (U.P.). Agromyzid popularly known as Ieafminers, are known to infest a wide range of cultivated plants like Lycopersicon esculentum (Linn.). The thimet 0.5% gave 17%, 1.0% gave 24%, 1.5% gave 41% and 2.0% gave 46% control in November-December 2006, while it was recorded 50% control during November- December 2007. The average relative humidity was 86%, while the temperature was recorded 19°C at the time of experimentations in both the years.